Kombinasi Pijat Oksitosin dan Lavender Oil pada Buteki dengan Masalah Menyusui Tidak Efektif - Ratna Ningsih; Rosnani Rosnani; Herawati Jaya (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: Breastfeeding problems, such as ineffective breastfeeding due to inadequate milk supply, significantly contribute to the failure of exclusive breastfeeding. This study aims to describe the nursing care application of combining oxytocin massage with lavender oil to overcome ineffective breastfeeding in postpartum mothers. . Methods: The research utilized a descriptive case study design with a nursing process approach involving two postpartum mothers as participants. Data were collected through observation using the LATCH assessment tool and interviews, while the intervention consisted of oxytocin massage using lavender oil as the massage medium for three consecutive days. Results: The results showed that both participants experienced an increase in breastfeeding status, characterized by breast milk beginning to flow smoothly, reduced maternal anxiety, and improved infant attachment. Both mothers were able to demonstrate the technique independently and reported feeling more relaxed after the intervention. Conclusion: The combination of oxytocin massage and lavender oil is effective in increasing milk production and overcoming ineffective breastfeeding problems in postpartum mothers.